Frequency of Apnea of Prematurity in Preterm Neonates Presenting at DHQ Hospital, Dera Ismail Khan - Ahlam, Madiha; Burki, Farmanullah; Ullah, Farid (Biological and Clinical Sciences Research Journal, 2025)
Apnea of prematurity is a common clinical problem in preterm neonates and may contribute to short-term morbidity in neonatal units. Local data on its frequency may help improve early recognition and monitoring in resource-limited settings. Objective: To determine the frequency of apnea of prematurity in preterm neonates presenting at DHQ Hospital, Dera Ismail Khan. Methodology: This study was conducted on 138 preterm neonates (gestational age <37 weeks) aged 1–25 days. Neonates with lung malformations, sepsis, or birth asphyxia were not included. This study was conducted at the Department of Pediatrics, DHQ Hospital, DI Khan, from 29-April-2024 to 29-October-2024. Apnea of prematurity was assessed in all patients, defined as cessation of breathing for>15 seconds, along with bradycardia (<100 bpm on electrocardiogram). SPSS 27 was used to analyze the collected data. Frequencies and percentages were calculated for apnea of prematurity; a chi-square test was conducted for stratification, with a p-value < 0.05 considered significant. Results: In the present study, the mean age of the neonates was 11.14 ± 7.20 days, and their mean birth weight was 2.38 ± 0.42 kg. Apnea of prematurity was diagnosed in 43 (31.2%) neonates. Significant associations were found between apnea and lower age (p=0.008) and lower birth weight (p=0.002). Conclusion: The frequency of apnea of prematurity in preterm neonates in the present study was 31.2%. The condition was significantly associated with lower birth weight and lower age.